FORMATION OF FINANCIAL RESULTS AND ITS THEORETICAL-METHODOLOGICAL ASPECTS - Shergozieva Mekhrinigor Sherqul qizi (American Journals, 2024)
Financial statements serve as a vital role into the inner workings of an enterprise or organization. They encapsulate the financial consequences of production, sales, management, and various other activities, culminating in either profit or loss. Analyzing these results through the lens of financial statements forms the bedrock for informed decision-making at all levels. By delving into the nuances of financial results and the guiding principles of accounting standards, this article aims to illuminate the intricacies of financial statement preparation and the diverse reports they encompass. Furthermore, it sheds light on the evolution, structure, and content of International Financial Reporting Standards (IFRS), highlighting its significant role in the global financial landscape. Within Uzbekistan, the application of IFRS has gained significant traction, as evidenced by the growing number of organizations adopting this robust framework. The article examines the various financial reports submitted by IFRS, providing crucial insights into the financial health and performance of these entities. By exploring the compelling advantages of IFRS, including enhanced transparency and comparability, the article underscores its potential to foster a more stable and efficient financial ecosystem. However, it also acknowledges the ongoing challenges and emerging trends within the IFRS landscape, providing context for potential future developments.Ultimately, understanding the intricate language of financial results, as elucidated through the prism of financial statements, empowers organizations to navigate the complex world of finance with greater confidence and achieve sustainable success. This knowledge not only informs critical decisions about their current state and efficiency but also paves the way for strategic planning and robust management practices, ensuring a vibrant and resilient future.
Keywords: Financial results, profit and loss, types of financial statements, financial position, financial analysis, international standards, GAAP, IFRS, management reporting, accounting, taxes, types of statements, stock market